2017
DOI: 10.1001/jamadermatol.2017.1547
|View full text |Cite
|
Sign up to set email alerts
|

Factors in Early Adolescence Associated With a Mole-Prone Phenotype in Late Adolescence

Abstract: Die Zahl der Muttermale im Kindesalter korreliert offenbar mit dem Risiko, später gehäuft ( atypische) Nävi zu entwickeln. Darauf weisen die Ergebnisse einer Studie hin, in der mehr als 400 Kinder von der achten bis zur elften Klasse dermatoskopisch überwacht wurden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 39 publications
(110 reference statements)
2
7
0
Order By: Relevance
“…Childhood is a period of susceptibility to the long-term harmful effects of sun-exposure [ 7 ], as evidenced by differences in melanoma-risk between child and adult migrants moving from high to lower latitudes [ 3 , 7 ]. Our results support the hypothesis that early sunburn influences the proliferation of melanocytic nevi, increasing melanoma-risk in sun-sensitive individuals [ 3 , 4 ], and are consistent with earlier findings from our entire cohort [ 5 , 6 , 8 ]; those of the SONIC childhood nevus cohort in the USA [ 7 , 26 ]; and the transient dermoscopic changes observed in UV-irradiated nevi [ 31 ], as well as a pooled-analysis of 5700 cases and 7216 controls (drawn from 13 studies) demonstrating that childhood sunburn increases melanoma-risk for the trunk and limbs by 50% and the head and neck by 40% [ 32 ]. However, lifetime number of painful sunburns experienced in the first three decades was not significantly related to the number of incident nevi of all sizes ( p = 0.079) or ≥2 mm ( p = 0.329) in our study, even though the trend was indicative of a dose-response.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Childhood is a period of susceptibility to the long-term harmful effects of sun-exposure [ 7 ], as evidenced by differences in melanoma-risk between child and adult migrants moving from high to lower latitudes [ 3 , 7 ]. Our results support the hypothesis that early sunburn influences the proliferation of melanocytic nevi, increasing melanoma-risk in sun-sensitive individuals [ 3 , 4 ], and are consistent with earlier findings from our entire cohort [ 5 , 6 , 8 ]; those of the SONIC childhood nevus cohort in the USA [ 7 , 26 ]; and the transient dermoscopic changes observed in UV-irradiated nevi [ 31 ], as well as a pooled-analysis of 5700 cases and 7216 controls (drawn from 13 studies) demonstrating that childhood sunburn increases melanoma-risk for the trunk and limbs by 50% and the head and neck by 40% [ 32 ]. However, lifetime number of painful sunburns experienced in the first three decades was not significantly related to the number of incident nevi of all sizes ( p = 0.079) or ≥2 mm ( p = 0.329) in our study, even though the trend was indicative of a dose-response.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings advance current knowledge by demonstrating that nevus-proneness and characteristics indicative of elevated melanoma-risk are evident before age 7 years, at least in Caucasians from tropical Australia’s UV-intense environment. Identifying those “at-risk” early in life provides greater opportunity to intervene with personalized sun-protection counselling in time to reduce risk [ 26 , 27 ] by slowing the rate of nevus-acquisition, which evidence suggests is a modifiable risk-factor [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Insight into the possible causes and prevention of melanoma is informed by a deeper understanding of the development of melanocytic nevi because nevi are an established risk factor for melanoma [7][8][9][10] and basal cell carcinoma, 11 and many of the same factors confer risk for nevi and skin cancers. [12][13][14][15][16][17][18][19][20] The extant evidence indicates that nevi increase with age [21][22][23][24][25][26][27][28] and are more numerous among boys than girls 20,21,23,25,27 (although this can vary by body site 24 ), those with lighter phenotypes (light skin, eyes, and hair), 21,[23][24][25]29,30 and those who receive higher levels of exposure to UV light. 20,24,27,[31][32][33][34] However, this evidence is based largely on studies that are cross-sectional, 24 are longitudinal but focused on a relatively short period of childhood or adolescence, 23,27,30 examined nevi intermittently across a range of years,…”
mentioning
confidence: 99%
“…Identification of high-risk demographic, phenotypic, or exposure groups has implications for tailoring interventions for skin cancer prevention. 21,22 A previous study reported median nevus counts among non-Hispanic white children aged 3 to 8 years in the Colorado Kids Sun Care Program cohort who were born in 1998 in the Denver region of Colorado and attended 1 or more annual skin examinations between 2001 and 2006. 25 In general, counts increased by 4 to 6 nevi each year.…”
mentioning
confidence: 99%